Two New Species of Chaetopteryx Stephens, 1837 from Turkey with a Description of the Unknown Female of C. bektasensis Sipahiler, 2008 (Trichoptera, Limnephilidae: Limnephilinae: Chaetopterygini) - Füsun Sipahiler (Psyche: A Journal of Entomology)
Two new species of Trichoptera from Turkey are described and illustrated: Chaetopteryx akgolensis sp.n. and Chaetopteryx sinopica sp.n. (Limnepphilidae). Both belong to the tribe Chaetopterygini in the Limnephilinae. C. akgolensis sp.n. is close to C. bektasensis Sipahiler, 2008, whereas C. sinopica sp.n. is closely related to C. nalanae Sipahiler, 1996. The previously unknown female of Chaetopteryx bektasensis Sipahiler, 2008 is described and figured.